2013
DOI: 10.1039/c3cc41576g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (E)-nitroolefins via decarboxylative nitration using t-butylnitrite (t-BuONO) and TEMPO

Abstract: Nitroolefins are usually synthesized using the Henry reaction. Here we report an alternative metal-free decarboxylative nitration protocol for the preparation of the nitroolefins from α,β-unsaturated carboxylic acids using t-butylnitrite (t-BuONO) and TEMPO. α,β-Unsaturated carboxylic acids bearing β-aromatic and β-heteroaromatic substituents gave (E)-nitroolefins exclusively under mild conditions. A radical based pathway has been proposed for this decarboxylative nitration reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 30 publications
2
69
0
1
Order By: Relevance
“…Melting points and NMR data of the synthesized β-nitrostyrenes were consistent with the literature values (Gairaud and Lappin, 1953; Somasekhara et al, 1971; Bose et al, 1992; Wang and Wang, 2002; Al-Zereini et al, 2007; Yan et al, 2008; Kumar et al, 2012; Manna et al, 2013; Cornell et al, 2014). …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Melting points and NMR data of the synthesized β-nitrostyrenes were consistent with the literature values (Gairaud and Lappin, 1953; Somasekhara et al, 1971; Bose et al, 1992; Wang and Wang, 2002; Al-Zereini et al, 2007; Yan et al, 2008; Kumar et al, 2012; Manna et al, 2013; Cornell et al, 2014). …”
Section: Resultssupporting
confidence: 88%
“…1-nitro-3-((E)-2-nitrovinyl)benzene (10) (Manna et al, 2013): IR (cm −1 ): 3003, 2875, 1694, 1521, 1057, 854; 1 H NMR (CDCl 3 , 400 MHz): δ 7.51 (t, J = 8.0 Hz, 1H), 7.69-7.71 (m, 1H), 7.72 (d, J = 12.0 Hz, 1H), 8.07–8.10 (m, 1H), 8.18 (d, J = 12.0 Hz), 8.28 (s, 1H); ESI-MS (m/z): 195 (M + +1); Anal. Calcd for (C 8 H 6 N 2 O 4 ): C, 49.49; H, 3.12; N, 14.43.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Maiti has shown that in the presence of stoichiometric amount of TEMPO, the reaction of tert-butyl nitrite with olefins can give rise to nitroalkenes. [15] Okamoto and Tanimoto have shown that using a Co complex as the catalyst, and BH 4 -as the hydrogen donor, the reaction of ethyl nitrite with styrenes can produce oximes as the exclusive product. [16] In 1998, Sugamoto was able to effect the same transformation using Et 3 SiH as the hydride donor employing Co Ⅱ (tpp) as the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…41 The reaction of a broad substrate scope of α,β-unsaturated carboxylic acids bearing aromatic and heterocyclic moieties smoothly proceeded under mild conditions and produced exclusively E-nitro compounds. 41 The reaction of a broad substrate scope of α,β-unsaturated carboxylic acids bearing aromatic and heterocyclic moieties smoothly proceeded under mild conditions and produced exclusively E-nitro compounds.…”
Section: Scheme 16mentioning
confidence: 99%